Simplified Compact Perovskite Solar Cells with Efficiency of 19.6% via Interface Engineering. Issue 1 (5th February 2020) - Li, Dedi; Liu, Changwen; Chen, Shi; Kong, Weiguang; Zhang, Haichao; Wang, Deng; Li, Yan; Chang, Jianhui; Cheng, Chun
Abstract : For the commercialization of perovskite solar cells (PSCs), it is more appealing to develop high‐performance simplified PSCs where perovskite films are just sandwiched between the back and front electrodes, in order to simplify the fabrication process and to reduce the cost. However, to date, this kind of devices shows rather low performance, and there are few researches on this subject. Herein, we report on a kind of compact PSCs (CPSCs) that are free of independent charge transport layers (CTLs). The devices are realized by the use of organic monolayer‐modified effective electrodes, along with the use of [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM)‐assisted anti‐solvent technique to obtain ultra‐thin ( 10 nm) PCBM‐embedded perovskite films. Compared to control devices, CPSCs achieve a promising champion power conversion efficiency of 19.6% with largely reduced hysteresis. Moreover, the unencapsulated CPSC shows good stability under ambient atmosphere, with only 10% efficiency loss after 60 days' storage. This work indicates that, by delicate design, CPSCs with smaller materials consumption in device architecture can perform competitively as conventional PSCs. Further reduction in the actual usage of costly CTL materials can be expected upon our CPSCs by developing more facile and economic methods to prepare ultra‐thin CTLs. Abstract : We report on a kind of compact PSCs (CPSCs) that are free of independent charge transport layers (CTLs). Compared to control devices, CPSCs achieve a promising power conversion efficiency of 19.6% with largely reduced hysteresis and enhanced stability.